Resistance, Reactance, and the Difficult Client - Thomas Dowd, E.; Sanders, Daniel (Canadian Journal of Counselling and Psychotherapy, 2007)
This article describes the effect of client resistance and reactance in the counselling and methods for assessing these phenomena. In addition, client symptoms are conceptualized as either ego-syntonic, where the symptom is consonant with the client's self-image, or as egodystonic, where the symptom is dissonant from the client's self-image. These concepts are then used in deriving counselling strategies for working with difficult clients according to a model that crosses high and low reactance with ego syntonicity dystonicity. According to this model, the least difficult clients are those whose reactance is low and whose symptoms are ego-dystonic. The most difficult clients are those whose reactance is high and whose symptoms are egosyntonic. Clients whose reactance is low and whose symptoms are ego syntonic or whose reactance is high and whose symptoms are ego-dystonic are moderately difficult. Counselling interventions designed for clients in each of the four categories are described.